Early detection of colon cancer by increased serum level of Krebs von den Lungen-6 in a patient with dermatomyositis-associated interstitial pneumonia - Fukuhara, Naoko; Tanino, Yoshinori; Sato, Suguru; Fukuhara, Atsuro; Uematsu, Manabu; Nikaido, Takefumi; Misa, Kenichi; Sato, Yasuko; Saito, Junpei; Wang, Xintao; Munakata, Mitsuru (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Krebs von den Lungen-6 (KL-6) is a high-molecular-weight glycoprotein which is elevated in serum of patients with interstitial pneumonia (IP). Serum KL-6 level is clinically used for the diagnosis of IP as well as the evaluation of its disease activity. KL-6 is originally identified when exploring novel soluble antigens in patients with lung cancer, and is known to be elevated in patients with several malignant tumors. The risk of malignant tumors is high in IP patients with polymyositis and dermatomyositis (PM/DM), and follow-up of KL-6 levels may allow earlier detection of such tumors. However, to date, there are only a few reports showing the usefulness of following-up serum KL-6 levels for finding malignant tumors in IP patients with PM/DM. Here, we described the first patient in whom increased serum KL-6 led to the diagnosis of colon cancer during follow-up of DM-associated IP.